The rise of free daily newspapers in Latin America - Bakker, Piet (2022)
Whereas most continents see circulation of newspapers drop, Latin America is one of the few areas in the world with rising newspaper circulation. A substantial part of this rise is caused by the introduction of free newspapers in a dozen countries on the continent. We map this development, discuss possible reasons for the rapid growth and try to answer whether this introduction has substitution effects on paid newspapers. The growth of this newformat is most probably caused by economic growth while we conclude that substitution is low, meaning that free dailies serve a new reading audience in Latin America.